Why Python is Most Famous (International Journal of Innovative Research in Computer Science & Technology, 2021)
We now have a plethora of programming  languages to meet our requirements, but the most pressing  issue is how to teach programming to beginners. We  recommend Python for this job in this article since it is a  programming language with a well-organized syntax and  strong capabilities for solving any problem. Furthermore,  it is extremely similar to basic math reasoning. In most top  institutions, Python is selected as the main programming  language for freshmen. Python makes it simple to write  code. In this article, we provide several computer code  samples developed in Java, C++, and Python, as well as a  comparison of the three languages.To begin, this article  discusses the benefits of Python over C++ and Java. The  results of a comparison of brief program codes written in  three distinct languages are then shown, followed by a  discussion of how pupils comprehend programming.  Finally, the experimental findings of students'  programming course success are shown.
Keywords: Application; Dynamic; Data; Python; Programming